Estudio del climaterio en Colombia (ECCO): evaluación del síndrome climatérico, riesgo cardiovascular y riesgo de fractura en mujeres en su periodo de transición 2011-2012 (2014)
Background. The female climacteric is associated with biological, psychological and social changes that can diminish the quality of life. Objective. To evaluate the quality of life in pre -and postmenopausal women in the rating scale at menopause (MRS), the cardiovascular and fracture risk in different hospitals of the country where queries are performed for Menopause. Material and methods. A multicenter study in which 545 medical records of women who suffering for neurovegetative symptoms between the ages of 45 and 70 years were collected. Some sociodemographic characteristics were evaluated and familial risk factors were investigated, cardiovascular risk in the Framingham scale and osteoporosis in the FRAX scale were done. Lipid profile values were quantified. Bone Densitometry was realized. Data were analyzed usingSPSS-12systemstatisticaltestsofsignificanceforthesecases(Studentt,SD,chi-square) and correlation. Results. Mean age was 53.94 years. By comparing older women and younger than 50 years in the rating scale of menopause (MRS) is detected: vasomotor symptoms (65.2% vs. 86.6%), tachycardia (39% vs. 64.4%), insomnia (56% vs. 75.7%), arthralgia (58.2% vs. 82.4%), depression (52.48% vs. 71.13%), irritability (55.3 % vs. 71.43%), anxiety (51.4 vs. 69.9%), asthenia (46.1% vs. 66.53), urinary symptoms (44.3 vs. 62.8%), decreased libido (42.1% vs. 50.0%), vaginal dryness (37.6% vs. 63.6 %), with significant differences in all variables (p < 0005-0001). Physical examination shows that the Media blood pressure was 137.4 mm Hg vs. 149.6 mm Hg, abdominal circunference 79.3 cm vs. 82.1 cm with significant differences (p < 0.001). BMI 26.46 vs. 26.95 with no difference (p < 0.323). Cardiovascular Risk 5 year (2.17 vs. 4.37) and 10 years (5.3 vs. 9.6) with significant differences (p < 0.001). Fracture risk in FRAX scale Column (15.8 vs. 18.4) (p < 0.03) and Femur (10.5 vs. 55.3) (p < 0.001). Conclusion. This multicenter study shows that with simple record oriented on Climacteric History, we may detect family and personal risk factors. Assess cardiovascular risk in Framingham and FRAX Fracture Risk scale and apply MRS scale for climacteric syndrome are useful tools in controlling women in their transition menopausal period.